Therapeutic and immunomodulatory effects of Bojungikki-tang on cancer: a scoping review - Eunbyul Cho; Se Won Na; Mi-Kyung Jeong (BMC Cancer, 2024)
Abstract Background Cancer remains a major global health concern, with conventional treatments often limited by side effects and resistance. Bojungikki-tang (BJIKT), a traditional herbal formula, has shown promise in alleviating cancer-related symptoms and enhancing anti-cancer effects when combined with conventional treatments. As immune checkpoint inhibitors (ICIs) have become the standard for cancer treatment, a combination of BJIKT and ICIs may exhibit immune-mediated anti-cancer effects. This review aims to summarize the recent evidence on BJIKT use in cancer treatment, investigate its immunomodulatory effects, and identify research gaps. Methods This review was conducted and reported following the Arksey and O’Malley framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Scoping Review. A comprehensive search of six electronic databases was conducted, and studies published between 2013 and 2022 were identified. Reports on oral administration of BJIKT to patients with cancer were included and analyzed by two reviewers. The extracted data were synthesized using descriptive reporting and meta-analysis. Results Overall, 56 studies met the inclusion criteria: 36 human studies, 14 experimental studies, and 6 reviews on clinical and preclinical investigations. The use of BJIKT in restoring immune function and improving fatigue, cancer-related fever, and quality of life after chemotherapy has been reported in clinical studies. The different medication forms of BJIKT included decoction, extract granules, pills, and water extract. The meta-analysis revealed a significantly higher Karnofsky Performance Scale score in the BJIKT plus chemotherapy group than in the chemotherapy alone group. Preclinical studies have demonstrated that BJIKT has anti-cancer effects, enhances gastrointestinal function and immunomodulatory effects, and supports favorable chemotherapy outcomes. Conclusion In recent clinical research on BJIKT, its impact on fatigue, quality of life, and alleviating cancer-related fever has mostly been examined. The direct anti-cancer activities and immunomodulatory mechanisms of BJIKT have been reported in preclinical studies; however, clinical research on BJIKT-induced enhancement of immune function is lacking. Further research on the efficacy and safety of ICI combined with BJIKT and the association of immunomarker changes with clinical outcomes is required to precisely identify the effect of BJIKT on immune system modulation.